Collections and collectors of antiquities in Basilicata between the 18th and early 20th centuries (ACME, 2022)
Until today no specific studies have yet been dedicated to the topic of private collecting of antiquities in Basilicata, as opposed to what happened in other regions of Southern Italy. Nevertheless, upon a careful examination of the bibliographic and archival sources – the latter mostly unpublished – available, it appears clear that Basilicata, so rich from an archaeological point of view, has actually known many important collecting experiences between the 18th and early 20th centuries. In the following pages I will try, for the first time, not only to explain the most relevant episodes and protagonists of local archaeological collecting in detail, but also to outline its general trends lines and follow its evolution in forms and contents over time. The aim of the article, in other words, is to propose an overall definition of the Lucanian “collecting culture”, which seems to fit perfectly and find its meaning in the broader Italian and European antiquarian culture during the period under review, offering, in the same time, new data for the knowledge of one of its most peculiar expressions: the practice of researching and collecting material evidences of the past in order to elaborate new identity constructions within the present.
Keywords: basilicata; modern age; magna grecia; antiquarian culture; archaeological collecting